2007
DOI: 10.1590/s0103-84782007000600007
|View full text |Cite
|
Sign up to set email alerts
|

Persistência do plano experimental em ensaios de avaliação de germoplasma elite de feijão

Abstract: A determinação do tamanho de parcela e do número de repetições é importante para a correta avaliação e diferenciação de genótipos. Assim, o planejamento de experimentos pode ser feito utilizando-se os resultados obtidos em ensaios já realizados. O objetivo deste trabalho foi verificar a repetibilidade do índice de heterogeneidade e do plano experimental, numa mesma área experimental com a cultura do feijão, durante sete anos (2000 a 2006). Quatorze ensaios de competição de germoplasma elite de feijão foram con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
3
0
1
Order By: Relevance
“…From the results presented in Table 4 we deduce, larger changes in the optimum plot size with changes of d and J than with changes of I, as observed by other researchers with different crops (Storck et al, 2007;Cargnelutti Filho et al, 2014;Souza et al, 2015). The results showed that Lin and Binns (1984) and Hatheway (1984) methods should be used together as observed by Storck et al (2007Storck et al ( , 2009.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…From the results presented in Table 4 we deduce, larger changes in the optimum plot size with changes of d and J than with changes of I, as observed by other researchers with different crops (Storck et al, 2007;Cargnelutti Filho et al, 2014;Souza et al, 2015). The results showed that Lin and Binns (1984) and Hatheway (1984) methods should be used together as observed by Storck et al (2007Storck et al ( , 2009.…”
Section: Resultssupporting
confidence: 79%
“…The results showed that Lin and Binns (1984) and Hatheway (1984) methods should be used together as observed by Storck et al (2007Storck et al ( , 2009. The results of the present Table 4.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Verificou-se que o CV foi o fator que mais influenciou o tamanho conveniente da parcela, pois, foram observados grandes aumentos no tamanho conveniente da parcela estimado com o aumento do CV, em qualquer combinação de d, I e r. Esses resultados assemelhamse aos obtidos por Muniz et al (2009), Oliveira et al (2011) e Silva (2009 (SILVA, 2009;STORCK et al, 2007), o que propicia maior eficiência do uso de parcelas pequenas associadas a um maior número de repetições, para detectar menores diferenças percentuais entre cultivares do que o uso de parcelas maiores com um menor número de repetições (SILVA, 2009). …”
Section: Resultsunclassified
“…It is worth noting that an increase in the number of replications was more efficient in reducing the value of d (increased experimental precision), when compared to an increase in the number of cultivars (Table 4), a fact also demonstrated by Donato et al, 2008, Storck, Bisognin and Oliveira, 2006and Storck et al 2007. …”
Section: Resultsmentioning
confidence: 65%